Italy in a European Context 2015
DOI: 10.1007/978-1-137-56077-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Reproductive Intentions in Europe

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…First and foremost, it predicts a positive effect of pollution on households' decisions regarding higher fertility. As mentioned above, existing analyses have already tested this result and have verified it empirically (Aggarwal et al., ; Bhattacharya and Innes, ; De Rose and Testa, ; Brauner‐Otto, ). Note, however, that all the mechanisms that are central to the emergence of this result in our model can also provide testable implications.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…First and foremost, it predicts a positive effect of pollution on households' decisions regarding higher fertility. As mentioned above, existing analyses have already tested this result and have verified it empirically (Aggarwal et al., ; Bhattacharya and Innes, ; De Rose and Testa, ; Brauner‐Otto, ). Note, however, that all the mechanisms that are central to the emergence of this result in our model can also provide testable implications.…”
Section: Introductionmentioning
confidence: 57%
“…Empirical evidence supporting the idea that various forms of environmental degradation can alter household decisions towards increased fertility is provided by Aggarwal et al. (), Bhattacharya and Innes (), De Rose and Testa () and Brauner‐Otto ().…”
Section: Introductionmentioning
confidence: 86%
“…In wealthier countries, results are also inconsistent. A 2011 study in Europe found an association between environmental concern and pro‐natalism (De Rose & Testa, 2015). In contrast, two small‐sample studies of Canadian college students found a negative association between environmental concern and fertility desires (Arnocky et al, 2012; Davis et al, 2019).…”
Section: Empirical Connections Between Environmental Attitudes and Fe...mentioning
confidence: 99%
“…The resources a potential parent needs are of a different nature: monetary support to reduce the general costs of rearing a child; informal childcare and help in household duties; or even only emotional support (Bühler & Philipov, 2005;Bernardi & Klaerner, 2014). The characteristics of the immediate living environment, that is the contextual dimensions closest to individuals, should be also considered (Bongaarts & Watkins, 1996;Lee et al, 1994;De Rose & Testa, 2016). In fact, the structural factors, such as the availability and affordability of housing, family-oriented services and infrastructure, or economic opportunities and constraints relate to the direct and indirect costs of children (Kulu & Vikat, 2007;Kulu, 2011;Kulu & Washbrook, 2014;Fiori et al, 2014).…”
Section: The Relationship Between Social Capital and Fertility: Liter...mentioning
confidence: 99%